Validitas Media M-Learning Berbasis Android Aritmatika Sosial Kelas VII MTs Negeri 1 Lampung Utara - Fhela Vhantoria Ningrum; Buana Jaya; Venty Meilasari (Eksponen, 2022)
The lack of knowledge that students can absorb on social arithmetic material which is conveyed only through photos of material has an impact on learning outcomes. The development of Android-based M-Learning media is deemed necessary to overcome the problem of low social arithmetic learning outcomes. This study aims to develop social arithmetic android-based M-Learning media for class VII students of Madrasah Tsanawiyah Negeri 1 North Lampung based on expert due diligence assessments. The research and development method used is the ADDIE model (analysis, design, development, implementation, and evaluation). The use of the ADDIE model in research and development is limited so that it is only the ADD (analysis, design, and development) stage. Time is the limit for the stages of becoming ADD. The types of data are quantitative data and qualitative data. Details of the validation results, the material expert validator gets a percentage score of 100% with the assessment criteria Very feasible, no revision needed, the decision from the media expert validator gets a score percentage of 92.8% with the assessment criteria very feasible, no revision needed, the decision from the expert validator language gets a percentage score of 87.3% with very decent assessment criteria, no need for revision. The results of research and development are products in the form of M-Learning based on social arithmetic android for class VII students of MTs Negeri 1 North Lampung with appropriate criteria based on expert judgment